LEGAL AND ORGANIZATIONAL BASIS CREATION AND ACTIVITY OF CONDOMINIUMS - Щербина, Богдан Сергійович; Бузун, Ольга Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: investigate the legal support for the establishment and operation of associations of co-owners of apartment buildings. Methods: method of analysis and synthesis of regulations, comparative analysis of Ukrainian legislation. Results: clarification of the problem and prospects for the development of condominiums, analysis of changes in improving the legal framework and implementation today. Discussion: the concept and formation of property in Ukraine; historical development of property; basic regulations; assessment of the formation of associations. The procedure for creating, approving the Statute of condominiums, state registration of the association of co-owners of an apartment building is in accordance with the laws of Ukraine and other regulations. Undoubtedly, such an association in accordance with the Law of Ukraine «On the association of co-owners of an apartment building» is a legal entity that has its own seal, as well as current accounts in the bank. Important for the functioning of condominiums is the Charter, which in turn is one of the main documents that has its own structure. The charter must meet the requirements of the law on and the standard charter. In addition, he may have provisions that are not provided by law, but do not contradict it. During the years of independence of our country there have been conflicts and problems in the legislative aspect regarding the activities of condominiums and such changes have brought both improvements and negative consequences from various quarters. Further research will allow to develop not only in the theoretical aspect of the formation of new condominiums, but also in practical action.